(untitled) (Perner’s Contacts, 2017)
The paper deals with air transport demand in Europe. Possible events that might influence air transport demand are explored. Specifically the influence of terrorist attacks is examined because number of attacks is constantly increasing worldwide. Effects on demand are explored in a short-time period after the terrorist attacks in Paris and Brussel on transport demand at these airports. To verify the influence of terrorist attacks on transport demand is used the one way ANOVA statistics.